2017
DOI: 10.1038/srep44679
|View full text |Cite
|
Sign up to set email alerts
|

Continuous transport of Pacific-derived anthropogenic radionuclides towards the Indian Ocean

Abstract: Unusually high concentrations of americium and plutonium have been observed in a sediment core collected from the eastern Lombok Basin between Sumba and Sumbawa Islands in the Indonesian Archipelago. Gamma spectrometry and accelerator mass spectrometry data together with radiometric dating of the core provide a high-resolution record of ongoing deposition of anthropogenic radionuclides. A plutonium signature characteristic of the Pacific Proving Grounds (PPG) dominates in the first two decades after the start … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 41 publications
2
17
0
Order By: Relevance
“…Additionally, plutonium may reach the slope by delayed transport from the shelf. : Plutonium activities and atom ratios observed in this study (Philippine Sea), compared to previous studies in Lombok basin (Pittauer et al, 2017), Okinawa Trough (Lee et al, 2004), South China Sea (Wu et al, 2014) and Sagami Bay (Zheng & Yamada, 2004).…”
Section: Regional Contextsupporting
confidence: 40%
See 2 more Smart Citations
“…Additionally, plutonium may reach the slope by delayed transport from the shelf. : Plutonium activities and atom ratios observed in this study (Philippine Sea), compared to previous studies in Lombok basin (Pittauer et al, 2017), Okinawa Trough (Lee et al, 2004), South China Sea (Wu et al, 2014) and Sagami Bay (Zheng & Yamada, 2004).…”
Section: Regional Contextsupporting
confidence: 40%
“…Clear PPG signals are also reported in sediments from the Sulu and South China Seas (Dong et al, 2010;Wu et al, 2014). Recently, the PPG derived transuranics were found in the sediments of the Lombok basin off the Indonesian island of Sumba (Steinke et al, 2014;Pittauer et al, 2017). The transport likely follows the pathway southward with the Mindanao Current, and further through the Maritime Continent.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…15,75,78 Report of the sedimentary inventory of 239,240 Pu in the Southern Hemisphere indicate lower levels. Pittauer et al 90 reported that the 239,240 Pu inventory in the Lombok basin of the India Ocean (10°S) was 219 Bq m -2 , which was sig nificantly higher than the global fallout value at this latitude. The distribution of the 239,240 Pu Figure 3.…”
Section: Distribution Of Pu In Marine Sedimentmentioning
confidence: 93%
“…1 The distribution of Pu concentration in the marine environment is influenced by ocean current distribution and biogeochemical cycles, and therefore, Pu isotopes are typically utilized to trace water mass exchange, particle scavenging and biogeochemical cycles. [2][3][4] Compared to 90 Sr (K d: 10-10 2 L kg -1 ) and 137 Cs (K d: 10 2 -10 3 L kg -1 ), Pu has a much stronger particle affinity in marine environments (K d: 10 4 -10 7 L kg -1 ) and thus can serve as a better tracer for indicating transport, scavenging and particle deposition. [5][6][7][8] To use Pu as a tracer for environmental process, the geochemical behavior of Pu should be understood and the analytical method for Pu need to be improved.…”
Section: Introductionmentioning
confidence: 99%